Is It Time for "Time-In"?: A Pilot Test of the Child-Rearing Technique - George W. Holden; Tricia Gower; Sharyl E. Wee; Rachel Gaspar; Rose Ashraf (MDPI AG, 2022)
Time-out, a mainstay of non-punitive discipline for over 60 years, has been criticized for isolating and distancing children from others. An alternative technique, one promoted by advocates of positive parenting practices, is labeled "time-in". This procedure is intended to help the child connect to the parent, communicate their feelings, and learn how to self-regulate. Although the technique has been advocated in the positive parenting literature since at least the 1990s, there are few empirical studies evaluating it. This pilot mixed-models study was designed as an initial test to determine whether mothers, following a brief training, would use the procedure over a two-week period, and how they would view it. Based on the daily reports as well as post-intervention interview of a small sample of mothers, the technique was evaluated as easy to use and effective. This study provides initial information about mothers' use of the technique and sets the stage for a comprehensive set of studies to rigorously test and evaluate the technique.